The making of living ḥadīth: a new direction of ḥadīth studies in Indonesia - Qudsy, Saifuddin Zuhri (Culture and religion, 2023)
Ḥadīth studies identifies Islamic practices that originate from the text of the ḥadīths or the traditions of the Prophet Muhammad. The term ‘living ḥadīth’ has emerged as a new direction to ḥadīth studies. This article seeks to explore the dynamics of living ḥadīths as they have emerged in and revitalised ḥadīth studies, especially within academic discourse of Indonesian Islamic universities. Important findings include that the living ḥadīth has become a subdiscipline of ḥadīth studies that examines on how Muslims interpret and express the ḥadīths in their daily lives, as well as how Indonesian Muslims link, communicate, and relate ḥadīths to local traditions and how local cultures assimilate and interact with the texts. This article also finds that the paradigm of living ḥadīth differs from the disciplines of sociology and anthropology of religion, presenting its epistemology through five areas of focus: practice, reception, text, transmission, and transformation.